Odpowiedzi

2010-02-28T18:30:35+01:00
2(a+b)-(a-2b)+(2a-1)-3=2a+2b-a+2b+2a-1-3=3a+4b-4=3×(-3)+4×1-4=-1


(x-y)×4-2x(x-y)+ x² (x-y)=4x-4y+x³-x²y
2010-02-28T18:40:19+01:00
2(a+b)-(a-2b)+(2a-1)-3= 2(-3+1)-(-3-2)+(2-1)-3=2(-2)+5+1-3=-4+3=-1


(x-y) razy 4 -2x razy (x-y)+ x do potęgi drugiej (x-y)= 4x+xkwadrat-2xkwadrat-xy-4x-xy+2xy+ykwadrat+4x-4y-2xkwadrat+2xy+xdo szescianu-xkwadraty=5xkwadrAT+4x+2xy-4y+ykwadrat+xdo szescianu-xkwadrat y
2010-02-28T18:46:46+01:00
B) 2(a+b)-(a-2b)+(2a-1)-3= 2a+2b-a+2b+2a-1= 2*(-3)+2-(-3)+2+2*(-3)-1= -6+2+3+2-6-1= 7-13= -6
c) 4(x-y)-2x(x-y)+x²(x-y)= 4x-4y-2x²-2y+x³-x²y= 4x-6y-2x²+x³-x²y